Solar-light Driven Degradation of Methylene Blue by Titanium Oxide Nanoparticles (TiO2 NPs) - Shahi, Dipal Kumar; Regmi, Shukra Raj; Shawad, Narendra Prakash; Khan, Nurul Hoda; Joshi, Padam Raj; Khatiwada, Lekha Nath; Adhikari, Rameshwar (Journal of Physical and Life Sciences, 2024)
Methylene blue is a common laboratory and textile dye that shows toxicity and carcinogenic activity in human health. In the present work, we have synthesized titanium oxide nanoparticles by the co-precipitation method through a controlled pH pathway for the degradation of methylene blue. The synthesized TiO2 NPs are characterized by UV Spectrophotometer, Fourier Transfer Infrared (FT-IR), Electron Dispersive X-ray (EDX), and X-RD Crystallography. The average diameter of the particle 16.27±12.80 nm is obtained by solving Debye Scherer’s equation with crystallinity 57.15%. The photocatalytic degradation is carried out at the solar intensity of 5.76±0.14 kWh and methylene blue degradation is recorded at 665 nm in UV-visible spectrophotometer. The result reveals that methylene blue is completely degraded in solar light within 110 minutes with 98% catalytic efficiency, but the dark medium degradation is not completed until 140 minutes and is limited to its 48% efficiency. The temperature-enhancing degradation in solar light is completed in 70 minutes with 98% efficiency. The catalytic efficiency of TiO2 NPs in light is superior to that in the dark, which explores its potential application as a photocatalyst.